Galectin-9 Expression Predicts Favorable Clinical Outcome in Solid Tumors: A Systematic Review and Meta-Analysis - Zhou, Xiaoxiang; Sun, Lejia; Jing, Dan; Xu, Gang; Zhang, Jinmei; Lin, Li; Zhao, Jingjing; Yao, Zhuoran; Lin, Hongfeng (Frontiers in Physiology, 2018)
Background and Objective: Galectin-9 (Gal-9) is one of the galectin family members which are known as proteins with β-galactoside-binding affinity. Accumulative evidence suggest that Gal-9 plays multifaceted roles in tumor biology. However, the prognostic significance of Gal-9 in solid cancer patients remains controversial. The objective of the study was to clarify the prognostic significance of Gal-9 in solid tumors via meta-analysis. Methods: We searched PubMed, Embase and the Cochrane library for studies that report the correlation between Gal-9 expression and prognosis or clinicopathological parameters in solid cancer patients from inception to October 2017, with no language restriction. We calculated pooled hazard ratio (HR) and 95% confidence interval (CI) to investigate the prognostic significance of Gal-9 expression in solid tumors. We also calculated Odds ratio (OR) to explore the association between Gal-9 expression and clinicopathological features. Results: We included Fourteen studies with 2326 patients in our meta-analysis. The synthetic results revealed that high Gal-9 expression indicated improved overall survival (OS; HR=0.70, 95% CI=0.51-0.71, P=0.006) but had no correlation with disease-free survival (DFS)/recurrence-free survival (RFS) (HR=0.85, 95% CI=0.51-1.41, P=0.527) in solid tumors. In stratified analyses, high Gal-9 expression was significantly correlated with improved OS in hepatocellular carcinoma and colon cancer and with improved DFS/RFS in gastric cancer and non-small cell lung cancer. In addition, ethnicity and the method of data extraction didn’t affect the positive prognostic values of high Gal-9 expression. Moreover, high Gal-9 expression was significantly correlated with a smaller depth of invasion (TⅠ/TⅡ vs. TⅢ/TⅣ, OR=2.80, 95% CI=1.97-3.96, P＜0.001), an earlier histopathological stage (Ⅰ/Ⅱ vs. Ⅲ/Ⅳ, OR=3.00, 95% CI=2.04-4.42, P＜0.001), negative lymph node metastasis (Presence vs. Absence, OR=0.47, 95% CI=0.25-0.89, P=0.020) and negative distal tumor metastasis (Presence vs. Absence, OR=13.85, 95% CI=3.50-54.76, P＜0.001). Conclusion: Gal-9 expression indicates beneficial outcome in patients with solid tumors and is correlated with the pathogenesis of solid tumors. Gal-9 may serve as a prognostic biomarker and an emerging therapeutic target against solid tumors.